Poly- and perfluorinated compounds activate human pregnane X receptor. (1st April 2017) - Zhang, Yi-Ming; Dong, Xiao-Yu; Fan, Li-Juan; Zhang, Zhi-Lei; Wang, Qian; Jiang, Nan; Yang, Xu-Shu
Highlights: All tested PFCs activated hPXR. The hPXR activity of the PFCs depends on the chain length and functional group. The H-bonding force seems to be crucial for hPXR potency of the PFCs. The hydrophobic interaction also play an important role for hPXR activity of PFCs. The mixtures involved by PFOA, PFNA and PFOS exert an additive effect on hPXR. Abstract: Poly- and perfluorinated compounds (PFCs), which have been detected worldwide in human blood, surface water and house dust, are suspected to induce potential endocrine-disrupting hormonal effects. In this study, cell-based reporter gene assays were used to determine the activity of a variety of PFCs against the human pregnane X receptor (hPXR) to identify the critical structural feature of PFCs related to their hPXR activity. Molecular docking studies combined with site-directed mutagenesis were employed to investigate the mechanism by which PFCs interact with and activate hPXR. We found that all tested PFCs can activate hPXR. The hPXR activity of the PFCs correlates with the carbon chain length and the functional group of the chemicals. Hydrogen bonding was characteristic of the interaction between PFCs and hPXR. We also identified the key residues within the hPXR ligand-binding pocket responsible for PFC-hPXR interaction. The outcome of the present study threw a light on the mechanism by which PFCs activate hPXR. PFCs may pose some potential endocrine-disrupting hormonal effects via activation of hPXR.